The Impact of Cost-of-Production Insurance on Input Expense of Fruit Growing in Ecologically Vulnerable Areas: Evidence from Shaanxi Province of China - Tao Li (MDPI AG, 2021)
Planting fruit trees in ecologically vulnerable areas is an effective approach to achieving the goal of ecological protection and improving farmers’ livelihoods. However, in ecologically vulnerable areas, farmers still face agricultural production risks such as natural disasters, diseases, and pests. In order to help fruit growers avoid these risks and ensure the sustainability of their livelihoods, the Chinese government has launched cost-of-production (COP) insurance in these areas. Although previous studies have shown that the purchase of revenue- or yield-based crop insurance will change insured farmers’ input expense of chemicals in agricultural production, the existing literature lacksa discussion on how COP insurance affects the input expense of chemicals in fruit growing. Here, we address the existing research gap from both theoretical and empirical aspects by conducting surveys in 1051 households of fruit growers in the Shaanxi province of China. Theoretical deduction reveals that the COP insurance on input expenditure of chemicals can have an increasing effect. Using the 2SLS model and empirical analysis, we found that the insured fruit growers spent more on using chemical fertilizers and pesticides compared to non-insured fruit growers. These findings demonstrate that the COP insurance’s positive marginal incentive to apply more input expense of chemicals in production dominates the negative moral hazard effect.